1995
DOI: 10.1016/s0166-4115(06)80077-4
|View full text |Cite
|
Sign up to set email alerts
|

Do the waves begin to waver? ERP studies of language processing in the elderly

Abstract: Until recently, relatively little research had been done on language processing in the elderly except as an adjunct to the study of aphasia. While language processes have usually been thought to be fairly impervious to aging, it is now clear that some changes do occur. Moreover, many of these changes often seem to be directly linked to changes in the efficacy of other cognitive operations affected by aging, particularly the active suppression of irrelevant information and the management of working memory (WM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 69 publications
3
6
0
Order By: Relevance
“…Between 0 and 250 ms poststimulus onset, both age groups show the characteristic series of evoked potentials elicited by visual stimuli, as displayed in Figure 1. Consistent with past studies of word-by-word reading examining sentence-final critical words, visual inspection reveals that posterior potentials are slightly reduced in size for older adults, whereas, anteriorly, the N1 is much larger in older compared to younger adults and the P2 is notably reduced (King & Kutas, 1995;Wlotko, Lee, & Federmeier, 2010). ERPs are overlapped for the two age groups at two frontal, central, and occipital sites in Figure 2.…”
Section: Erpssupporting
confidence: 86%
“…Between 0 and 250 ms poststimulus onset, both age groups show the characteristic series of evoked potentials elicited by visual stimuli, as displayed in Figure 1. Consistent with past studies of word-by-word reading examining sentence-final critical words, visual inspection reveals that posterior potentials are slightly reduced in size for older adults, whereas, anteriorly, the N1 is much larger in older compared to younger adults and the P2 is notably reduced (King & Kutas, 1995;Wlotko, Lee, & Federmeier, 2010). ERPs are overlapped for the two age groups at two frontal, central, and occipital sites in Figure 2.…”
Section: Erpssupporting
confidence: 86%
“…Research on other kinds of processes needed to build a message-level representation has not been as well developed as in the use of semantic information during comprehension. However, King and Kutas (1995) show similar use of syntactic information by younger and older adults (modulated by working memory) and relate these findings to behavioral work (see, e.g., Kemper and Herman 2006). Similarly, Kemmer et al (2004) observed that older adults showed no difference in the size or timing of the P600 response, an ERP effect sensitive to grammaticality.…”
Section: Building a Message-level Representationsupporting
confidence: 60%
“…The characteristics of ERPs that make them so suitable for studying language also make them particularly useful for studying age-related changes in comprehension (see also King and Kutas 1995). It is clear that aging has differential effects on cognitive subprocesses, and ERPs provide specific indices that allow these effects to be examined independently but in tandem.…”
Section: Electrophysiology Of Language and The Aging Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…The N400 response to written words is sensitive to normal aging: N400 latency increases at ~2 ms/year and N400 amplitude decreases at ~0.07 μV/year across the adult lifespan [64, 65]. From ERP studies of semantic memory (reviewed below), it is apparent that the N400 is usually abnormal in AD, typically reduced in amplitude and delayed in latency beyond that seen in normal aging.…”
Section: N400 In Alzheimer’s Diseasementioning
confidence: 99%